2013
DOI: 10.1057/jphp.2013.47
|View full text |Cite
|
Sign up to set email alerts
|

The case for stringent alcohol warning labels: Lessons from the tobacco control experience

Abstract: Like cigarettes, alcohol is a social drug associated with considerable health and social costs. Relative to cigarettes, regulators worldwide have imposted very modest restrictions in its advertisements. Studies on alcohol health warnings show that they do not have a strong effect on influencing recall, perceptions, and behaviors. Poorly visible and ambiguous health warnings plus the absence of pictorial warnings muddy previous studies. This study takes a different approach, extracting lessons from cigarette he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 21 publications
1
35
1
Order By: Relevance
“…Similar results were found by previous research [39,40,41] concluding that Australian university students may consider warning labels ineffective because they do not perceive themselves to be personally vulnerable to the long-term consequences of alcohol use, or do not perceive such consequences to be relevant to them at this point in their lives, attaching more weight to the short-term than long-term consequences of their decisions. In addition, we reveal that young individuals attach more emotional impact to the negative framed warning (logo with the wrecked car) rather than the generic ones, confirming results from previous research [8,22]. …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results were found by previous research [39,40,41] concluding that Australian university students may consider warning labels ineffective because they do not perceive themselves to be personally vulnerable to the long-term consequences of alcohol use, or do not perceive such consequences to be relevant to them at this point in their lives, attaching more weight to the short-term than long-term consequences of their decisions. In addition, we reveal that young individuals attach more emotional impact to the negative framed warning (logo with the wrecked car) rather than the generic ones, confirming results from previous research [8,22]. …”
Section: Discussionsupporting
confidence: 89%
“…Alcohol warning labels are intended to increase knowledge and attitudes regarding the harmful consequences of alcohol use and promote changes in consumption behaviour [20]. Although there is no substantial evidence in the literature on the effectiveness of alcohol warning labels in changing behaviour, especially among groups at risk [22,23,24,46], previous research revealed that this could be due to narrow implementation, to the generic nature of the messages used, and to their poor visibility [21,22,28,46]. In this regard, in order to increase the likelihood of alcohol warning messages being perceived as relevant, they need to be congruent with the beliefs of the target audience [9,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other researchers observed limited or no effect of public health campaigns or responsible drinking statements on drinking behavior (see Agostinelli & Grube, 2002 for a review), or even unanticipated effects, such as increased alcohol consumption (Moss et al, 2015) or reduced negative attitudes toward alcohol (Brown, Stautz, Hollands, Winpenny, & Marteau, 2016). Some researchers suggest that the limited effectiveness of responsible drinking statements might be attributed to their design and content, as they generally provide little information about alcohol-related harms and provide no clear goals for behavior change (Al-hamdani, 2014; Martin-Moreno et al, 2013; Wilkinson & Room, 2009). …”
mentioning
confidence: 99%